Contribuição ao conhecimento químico da flora acreana: Protium hebetatum Daly, Protium heptaphyllum(Aublet) Marchand subsp. ulei (Swat) Daly e Protium heptaphyllum (Aublet) Marchand subsp. heptaphyllum - Marques, Délcio Dias (2010)
This work presents study phytochemistry of three species of plants of the family Burseraceae: Protium hebetatum Daly (PHB), Protium heptaphyllum (Aublet) Marchand subsp. ulei (Swat) Daly (PHU) and the Protium heptaphyllum (Aublet) Marchand subsp. heptaphyllum (PHH), known, at random, as pitch, pitch-white and almécego. The species were collected in the municipal district of Cruzeiro do Sul, Acre, Brazil. Of the resin of PHB, were obtained three binary mixtures of triterpenes pentacyclics of the series oleanane/ursane: 3-oxoolean-12-ene and 3-oxours-12-ene; 3ß-hydroxyolean-12-ene and 3ß-hydroxyurs-12-ene; 3ß,16ßdihydroxyolean- 12-ene and 3ß,16ß-dihydroxyurs-12-ene; and four triterpenes tetracyclic of the series tirucallane: 3-oxotirucalla-8,24-dien-21-oic acid, 3a-hydroxytirucalla-8,24-dien-21-oic acid, 3a-acetoxytirucalla-8,24-dien-21-oic acid and the 3a-hydroxytirucalla-7,24-dien-21-oic acid. Of the epicuticular wax of the leaves of PHB were extracted mixtures of three hydrocarbons: heptacosane, hentriacontane and tritriacontane, and mixture of ethyl ester, as main constituent, the ethyl hexadecanoate. Of the resin of PHU were obtained two binary mixtures of triterpenes pentacyclics of the series oleanane/ursane: 3-oxoolean-12-ene and 3-oxours-12-ene; 3ß-hydroxyolean-12-ene and 3a-hydroxyurs-12-ene; three triterpenes tetracyclics of the series tirucallane: 3-oxotirucalla-8,24-dien-21-oic acid, 3ahydroxytirucalla- 8,24-dien-21-oic acid and the 3a-hydroxytirucalla-7,24-dien-21-oic acid and one triterpene pentacyclic of the series friedelane: D:A-friedoolean-3-one. From the essential oil of PHU, were isolated two monoterpenes: the terpinolene and the p-cymen-8-ol. The essential oil of the resins of PHB, PHU and PHH, presented as main constituent a-pinene (21.28%), terpinolene (42.31%) e p-cymene (31.50%), respectively. Those oils showed biological activity to the microorganism: Bacillus subtilis, Klebsiella pneumoniar, Staphylococcus aureus, Escherichia coli, Nycobacterium phlei. Specifically, the essential oil of PHB was analyzed his activity against larva of the mosquito Aedes aegypti, presenting CL50 = 270.32 ppm, considered don’t activate. Some reactions were performed with the intention of structural proof, as well as, to detach, in part, the chemistry. Finally, was verified the possibility of using the immobilized enzymes of the resin of PHB as biocatalyst, in acetylation reaction.